2018
DOI: 10.1149/2.0101805jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Evaporation Driven Micro/Nanofluidic Pumping Device

Abstract: A compact portable nanofluidic pump that enables precise manipulation of ultra-small amount of liquid is highly desirable for the trend in miniaturization. Here we develop an integrated micro/nanofluidic pumping device utilizing nanopillar structures with diminishing intervals and locally controlled evaporation. A continuous and steady flow rate of 2.7 pL/s was achieved for more than 12 h without external mechanical power source. The liquid transports in the nanofluidic channels were controllable by adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Pumps to control fluid in a nanochannel are also rarely found. For 2D nanochannels, passive and electrokinetic pumps have been reported. Meanwhile, due to technical difficulties in nanofabrication, only one mechanical pump has been reported that fits a 1D nanochannel .…”
Section: Fundamental Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pumps to control fluid in a nanochannel are also rarely found. For 2D nanochannels, passive and electrokinetic pumps have been reported. Meanwhile, due to technical difficulties in nanofabrication, only one mechanical pump has been reported that fits a 1D nanochannel .…”
Section: Fundamental Technologiesmentioning
confidence: 99%
“…60 Pumps to control fluid in a nanochannel are also rarely found. For 2D nanochannels, passive 61 and electrokinetic 62…”
mentioning
confidence: 99%
“…For example, many nanoflow studies have focused on using carbon nanotubes to transport water flows 1. 16 Scientists use evaporation, 17 , 18 electroosmotic flow, 19 high voltage, 20 ions, 21 nanowires, 22 surface charge, 23 and even large HPLC pumps 24 to control the nanometer flow. Nanofluidic technology also needs microfluidic technology, such as temperature-controlled peristaltic pumps, 25 air-controlled valves, 26 microfluidics combined with membranes, 27 170 V silicon dioxide thin film deformable pumps, 28 and 4W ultrasonic drives.…”
Section: Introductionmentioning
confidence: 99%
“…Other nano-scale pumps have been demonstrated that use evaporation [11] and external pressure [12]. Driving flow with evaporation can be convenient because no external power is needed to drive flow.…”
Section: Introductionmentioning
confidence: 99%
“…Driving flow with evaporation can be convenient because no external power is needed to drive flow. However, it is a loosely controlled fluid transport mechanism that varies with the temperature, relative humidity, and even airflow over the exit reservoir [11]. Similarly, devices that generate flow based on external pressure mandate additional supporting equipment, which hinders miniaturization.…”
Section: Introductionmentioning
confidence: 99%